Epistemologi Pendidikan Qur'ani: Telaah terhadap Konsep Ta'lim, Tarbiyah, dan Ta'dib dalam Al-Quran - Abdul Qodir; Asrori, Muhammad (Pustaka Peradaban, 2025)
Qur'anic educational epistemology is a significant field of study that seeks to understand the concept of education as derived from divine revelation. This article aims to critically examine three principal concepts in Qur'anic education—ta'lim, tarbiyah, and ta'dib—based on a review of the Qur'anic text. Using a literature-based methodology, this study analyzes relevant Qur'anic verses and interpretations by classical and contemporary mufassirs (Qur'anic interpreters). The findings indicate that ta'lim emphasizes knowledge transmission, tarbiyah focuses on the holistic development of human potential, and ta'dib reflects the internalization of values and character formation. The integration of these three concepts forms a holistic and comprehensive framework for Qur'anic education. This article also explores the relevance of these concepts in addressing modern educational challenges, particularly in shaping insan kamil (the perfect human being), who is characterized by and oriented towards divine values. This study is expected to provide both theoretical and practical contributions to the development of a Qur'an-based Islamic education system. Epistemologi pendidikan Qur'ani merupakan cabang kajian penting dalam memahami konsep pendidikan yang bersumber dari wahyu. Artikel ini bertujuan mengkaji secara kritis tiga konsep utama dalam pendidikan Qur'ani, yaitu ta'lim, tarbiyah, dan ta'dib, berdasarkan tinjauan terhadap teks Al-Qur'an. Melalui metode studi pustaka, penelitian ini menganalisis ayat-ayat Al-Qur'an yang relevan serta interpretasi dari para mufassir klasik dan kontemporer. Hasil kajian menunjukkan bahwa ta'lim menekankan aspek transmisi ilmu pengetahuan, tarbiyah berfokus pada pengembangan potensi manusia secara holistik, dan ta'dib mencerminkan internalisasi nilai serta pembentukan akhlak. Integrasi ketiga konsep ini membentuk kerangka pendidikan Qur'ani yang holistik dan komprehensif. Artikel ini juga membahas relevansi konsep-konsep tersebut dalam menghadapi tantangan pendidikan modern, khususnya dalam membentuk insan kamil yang berkarakter dan berorientasi pada nilai-nilai ilahiyah. Kajian ini diharapkan memberikan kontribusi teoretis dan praktis dalam pengembangan sistem pendidikan Islam berbasis Al-Qur'an.